Acute ammonia poisoning in dolly varden char (Salvelinus malma) and effect of methionine sulfoximine. Issue 101 (June 2020) - Zhu, Xingzun; Li, Ming; Liu, Bao
Abstract: Ammonia is toxic to most bony fishes. However, little information is available on the toxicology mechanisms induced by ammonia and the means to mitigate the effects by various fishes. In this study, four groups of experiments were designed and carried out to test the response of dolly varden char to ammonia toxicity and their mitigation through methionine sulfoximine (MSO). NaCl group was injected with NaCl, NH3 group was injected with ammonium acetate, NH3 +MSO group was injected with ammonium acetate and MSO, MSO group was injected with MSO. Results showed that ammonia toxicity could lead to blood deterioration (elevation in white blood cell and blood ammonia), free amino acid imbalance (elevation in glutamine, glutamate, arginine and ornithine, coupled with reduction of citrulline and aspartate), ammonia metabolism enzyme activity inhibition (reduction in carbamyl phosphate synthetase, ornithine transcarbamylase and arginase), oxidative stress (reduction in superoxide dismutase, catalase and glutathione peroxidase) and immunosuppression (reduction in lysozyme, 50% hemolytic complement, total immunoglobulin and phagocytic index), but the MSO can eliminate fatal effect of oxidative damage. In addition, ammonia poisoning could induce down-regulation of antioxidant enzymes coding genes ( SOD, CAT and GPx ) and up-regulation of inflammatory cytokine genes ( TNFα, IL-1β and IL-8 ) transcription, suggesting that immunosuppression and inflammation may relate to oxidative stress in fish. Highlights: Ammonia poisoning induces oxidative stress, immunosuppression and inflammation. The immunosuppression and inflammation may relate to oxidative stress in fish. The MSO can eliminate fatal effect of oxidative damage.